Internal migration age patterns and the transition to adulthood: Australia and Great Britain compared - Bernard, Aude; Charles-Edwards, Elin; Bell, Martin (My University, 2016)
Life-course transitions are important drivers of mobility, resulting in a concentration of migration at young adult ages. While there is increasing evidence of cross-national variations in the ages at which young adults move, the relative importance of various key life-course transitions in shaping these differences remains poorly understood. Prior studies typically focus on a single country and examine the influence of a single transition on migration, independently from other life-course events. To better understand the determinants of cross-national variations in migration ages, this paper analyses for Australia and Great Britain the joint influence of five key life-course transitions on migration: (1) higher education entry, (2) labour force entry, (3) partnering, (4) marriage and (5) family formation. We first characterise the age profile of short- and long-distance migration and the age profile of life-course transitions. We then use event-history analysis to establish the relative importance of each life-course transitions on migration. Our results show that the age structure and the relative importance of life-course transitions vary across countries, shaping differences in migration age patterns. In Great Britain, the strong association of migration with multiple transitions explains the concentration of migration at young adult ages, which is further amplified by the age-concentration and alignment of multiple transitions at similar ages. By contrast in Australia a weaker influence of life-course transitions on migration, combined with a dispersion of entry into higher education across a wide age range, contribute to a protracted migration age profile. Comparison by distance moved reveals further differences in the mix of transitions driving migration in each country, confirming the impact of the life-course in shaping migration age patterns.
Keywords: Life Events -- Immigration / newly arrived migrants; Disadvantage, adversity and resilience; Life Events; Immigration / newly arrived migrants; Dsiadvantage, adversity and resilience; Adversity and resilience